2014
DOI: 10.3389/fpls.2014.00196
|View full text |Cite
|
Sign up to set email alerts
|

The activity of SnRK1 is increased in Phaseolus vulgaris seeds in response to a reduced nutrient supply

Abstract: Phaseolus vulgaris seeds can grow and develop at the expense of the pod reserves after the fruits have been removed from the plant (Fountain etal., 1989). Because this process involves sensing the reduction of nutrients and the remobilisation of pod reserves, we investigated the effect on sucrose non-fermenting related kinase 1 (SnRK1) activity during this process. Bean fruits removed from the plant at 20 days after flowering (DAF) demonstrated active remobilisation of nutrients from the pod to the seeds. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Walls of long and small pods did not show significant differences in starch concentration between treatments or during the light-dark cycle (Figure 3). These results are consistent with those obtained by [15], in which pods of common bean in the early stages of development showed lower starch concentration than did those in the advanced developmental stage. In contrast, Ref.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Walls of long and small pods did not show significant differences in starch concentration between treatments or during the light-dark cycle (Figure 3). These results are consistent with those obtained by [15], in which pods of common bean in the early stages of development showed lower starch concentration than did those in the advanced developmental stage. In contrast, Ref.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the physiological responses to drought in the pod wall may be due to the adjustment of metabolism to maintain homeostasis and seed filling. Further studies have demonstrated that the pod wall accumulates starch during the early stages of pod development [15]. For instance, [16] reported that pods accumulate starch in response to drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…Like their orthologs in fungi and animals, SnRK1s in plants function as the principle regulators of cellular energy homeostasis. SnRK1 activity can be activated by low nutrient stress or energy starvation as a result of prolonged darkness, hypoxia, or chemical inhibition of photosynthesis and can be inhibited by exogenous sucrose or glucose (Ananieva et al, 2008;Baena-Gonza ´lez et al, 2007;Bledsoe et al, 2017;Coello and Martı ´nez-Barajas, 2014;Nunes et al, 2013a). Once activated, SnRK1 kinases globally upregulate catabolic activities and repress anabolic processes (Baena-Gonza ´lez et al, 2007).…”
Section: Stress Sensing and Early Signalingmentioning
confidence: 99%
“…In plants, it was suggested that TAP46 acts as an inhibitor of PP2A activity. However, the exact effects on phosphatase modulation [192,193] Summary of studies on TOR and/or SnRK1 pathways associated with abiotic stress responses (direct or indirect evidences). Research works not addressing abiotic stresses were not included in this table.…”
Section: Downstream Targets Of Tor Kinasementioning
confidence: 99%